Understanding why an active video game intervention did not improve motor skill and physical activity in children with developmental coordination disorder: A quantity or quality issue? - Howie, Erin; Campbell, Amity; Abbott, R.; Straker, Leon (Pergamon Press, 2016)
BACKGROUND: Active video games (AVGs) have been identified as a novel strategy to improve motor skill and physical activity in clinical populations. A recent cross-over randomized trial found AVGs to be ineffective at improving motor skill and physical activity in the home-environment for children with or at-risk for developmental coordination disorder (DCD). AIMS: The study purpose was to better understand why the intervention had been ineffective by examining the quantity and quality of AVG play during an AVG intervention for children with or at-risk for DCD. METHODS AND PROCEDURES: Participants (n=21, ages 9-12) completed the 16 week AVG intervention. Detailed quantitative and qualitative data were systematically triangulated to obtain the quantity of exposure (AVG exposure over time, patterns of exposure) and quality of use (game selection, facilitators and barriers to play). OUTCOMES AND RESULTS: The median AVG dose (range 30-35min/day) remained relatively stable across the intervention and met the prescribed dose. Play quality was impacted by game selection, difficulty playing games, lack of time, illness, technical difficulties and boredom. CONCLUSIONS AND IMPLICATIONS: The ineffectiveness of a home-based AVG intervention may be due to quality of play. Strategies to improve the quality of game play may help realize the potential benefits of AVGs as a clinical tool for children with DCD.